Modeling Sporadic Progressive Supranuclear Palsy in 3D Midbrain Organoids: Recapitulating Disease Features for In Vitro Diagnosis and Drug Discovery - Parrotta, Elvira Immacolata; Lucchino, Valeria; Zannino, Clara; Valente, Desirèe; Scalise, Stefania; Bressan, Davide; Benedetto, Giorgia Lucia; Iazzetta, Maria Roberta; Talarico, Mariagrazia; Gagliardi, Monica; Conforti, Francesco; Di Agostino, Silvia; et al. (Annals of neurology, 2025)
Objective Progressive Supranuclear Palsy (PSP) is a severe neurodegenerative disease characterized by tangles of hyperphosphorylated tau protein and tufted astrocytes. Developing treatments for PSP is challenging due to the lack of disease models reproducing its key pathological features. This study aimed to model sporadic PSP‐Richardson's syndrome (PSP‐RS) using multi‐donor midbrain organoids (MOs). Methods The MOs were generated by pooling induced pluripotent stem cells (iPSCs) from 4 patients with sporadic probable PSP‐RS and compared them with MOs from 3 healthy control (HC) subjects. We performed comprehensive analyses of MOs over 120 days to assess neuronal death, reactive gliosis, and the accumulation of 4R‐tau and hyperphosphorylated tau forms (pThr231, pSer396, pThr181, and pSer202/pThr205 [AT8]) using immunofluorescence microscopy and Western blot. On day 90, immunohistochemical analysis using pSer396 and AT8 antibodies was conducted to assess disease pathology. Results PSP‐derived MOs showed progressive size reduction compared with HC‐derived MOs, linked to upregulated apoptosis‐related mRNA markers. Dopaminergic neuron degeneration was marked by decreased tyrosine hydroxylase (TH) and increased neurofilament light chain (NfL). Immunofluorescence and Western blot revealed accumulation of all investigated tau forms with a peak at 90 days, along with a significant rise in GFAP‐positive cells in PSP‐derived MOs. Immunochemistry confirmed typical PSP histological alterations, such as neurofibrillary tangles and tufted‐shaped astrocytes, absent in HC‐derived organoids. Interpretation We developed a robust in vitro PSP model reproducing the key molecular and histologic features of the disease. This result holds promise for advancing basic and clinical research in PSP, paving the way for in vitro molecular diagnosis and identification of novel therapeutic targets. ANN NEUROL 2025;97:845–859